Complexos de cobre (II) com bases de Schiff tridentadas, tipo ONN e tetradentadas simétricas e assimétricas, tipo ONNO: síntese e caracterização e estudos como catalisadores na oxidação de catecóis - Paulo, Luciana Batista de (2011)
Salen-type complexes are an important class of coordination compounds and are used as catalysts in various homogeneous and heterogeneous systems. Complexes of transition metals participate in many chemical processes, which make the study of these complexes very interesting. Research shows that the complexes of salen [salen = N, N'-ethylenebis (salicilidenoamina)] are efficient catalysts. Some compounds of this type have been investigated as catalysts for the oxidation of catechol. In this work three types of compounds the tetradentate ligands and symmetrical complexes, tridentate complexes and the asymmetric tetradentate complex, were synthesized. The series provided satisfactory yields. The compounds synthesized in this work were characterized by melting point, elemental analysis, vibrational spectroscopy in the IR region, absorption spectra in the UV-vis, conductivity measurements and solubility. The ligands were also characterized by nuclear magnetic resonance. From these characterizations, comparisons were made with respect to the effects of the substituents on the aromatic ring within the same series of compounds and also compared the results obtained for different lines of work. The kinetics was performed using a spectrophotometer, following the formation of the product derived from oxidation of 3,5-di-tert-butylcatechol at 400 nm. Among the complexes showed catalytic activity are the symmetrical complex [Cu (salen)], kcat = 2.6 x10-2 s-1, Vmax = 1.74 x10-7 mol L-1 s-1 and the complex asymmetric [Cu (3.5 Brsalen)]ass, kcat = 4.1 x10-2s-1, Vmax = 2.72 x10-7 mol L-1 s-1 and [Cu (3.5 Br4MeO-3, 5Br'salen) ]ass, kcat = 5.2 x10-2 s-1, Vmax = 3.39 x10-7 mol L-1 s-1.